Undergraduate and graduate physicist women: a comparative statistical analysis - Cerón Loayza, María Luisa (2019)
A comparative statistical analysis carried out at the Faculty of Physical Sciences, UNMSM, allows realize that there exists a marked disproportion between the numbers of admitted female and male students at the graduate level. Likewise, a similar situation is observed between the numbers of admitted and graduated female undergraduate students. These results based on statistical data verify that this eld of science continues to be masculinized.